THE ROLE OF THE EXTERNAL AUDITOR IN DETERMINING THE FAIR VALUE VALUES ACCORDING TO THE AUDITING STANDARD NO. (540) AN ANALYTICAL STUDY OF IRAQI AUDIT COMPANIES (World Bulletin of Social Sciences, 2023)
The research aims to demonstrate the role of the external auditor in verifying the validity of the estimates of the value of the material evidence by the Department under the International Audit Standard No. ( 540), which proved the existence of a response method between the software risk and the need and existence of the audit evidence when the audit was carried out on special equipment for microwave equipment The following interview was conducted directly in the form of a report from the Commercial Bank and a tool of the board of directors indicating that the external audit mechanism is based on the international audit ( 540 ) language of the Department of Finance and technical assessment the fair value of the audit reports is based on the quality of the audit reports and is determined by the risk of identifying errors or material misstatements in the financial statements